2023
DOI: 10.3390/f14040685
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microbial Communities on Elevational Gradient Adaptation Strategies of Pinus yunnanensis Franch. and Pinus densata Mast. in a Mixed Zone

Abstract: Pinus densata Mast. is considered a homoploid hybrid species that originated from the putative parent species Pinus tabuliformis Carr. and Pinus yunnanensis Franch., but the mechanism of the adaptive differentiation of P. densata and its parents in native habitats has not been reported. Therefore, the overlapping distribution areas between P. densata and P. yunnanensis in the heart of the Hengduan Mountains were chosen. The adaptive differentiation mechanism of the homoploid hybrids and their parents with resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 71 publications
(92 reference statements)
1
2
0
Order By: Relevance
“…The results showed that the composition of rhizosphere soil and root endophytes were significantly different. In agreement with most of the literature, the results show that the endophytes were not simply random or changed according to the rhizosphere soil microbial pool gradient, but were actively recruited [34,35]. The composition of soil microorganisms was consistent with previous reports.…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that the composition of rhizosphere soil and root endophytes were significantly different. In agreement with most of the literature, the results show that the endophytes were not simply random or changed according to the rhizosphere soil microbial pool gradient, but were actively recruited [34,35]. The composition of soil microorganisms was consistent with previous reports.…”
Section: Discussionsupporting
confidence: 92%
“…Another factor that impacts soil quality and health is soil erosion, which can have detrimental effects on forest productivity due to the loss of soil water and nutrients [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…As environmental conditions shift along elevation gradients, plant hosts may need to adapt and recruit different microbial symbionts to maintain their symbiotic relationships. The availability and composition of microbial symbionts may vary with elevation due to the altered soil characteristics and associated microclimatic conditions [8].…”
Section: Introductionmentioning
confidence: 99%